Specific fruit but not total fruit intake during early pregnancy is inversely associated with gestational diabetes mellitus risk: a prospective cohort study. Issue 13 (5th September 2021) - Sun, Hong; Dong, Hongli; Zhang, Yiqi; Lan, Xi; Pang, Xinxin; Cai, Congjie; Bai, Dan; Zhang, Ju; Li, Fei; Zeng, Guo
Abstract: Objectives: Fruit intake may influence gestational diabetes mellitus (GDM) risk. However, prospective evidence remains controversial and limited. The current study aimed to investigate whether total fruit and specific fruit intake influence GDM risk. Design: A prospective cohort study was conducted. Dietary information was collected by a 3-d 24-h dietary recall. All participants underwent a standard 75-g oral glucose tolerance test at 24–28 gestational weeks. Log-binomial models were used to estimate the association between fruit intake and GDM risk, and the results are presented as relative risks (RR) and 95 % CI. Setting: Southwest China. Participants: Totally, 1453 healthy pregnant women in 2017. Results: Total fruit intake was not associated with lower GDM risk (RR of 1·03 (95 % CI 0·83, 1·27) ( P trend = 0·789)). The RR of GDM risk was 0·73 for the highest anthocyanin-rich fruit intake quartile compared with the lowest quartile (95 % CI 0·56, 0·93; P trend = 0·015). A higher grape intake had a linear inverse association with GDM risk (Q4 v. Q1: RR = 0·65; 95 % CI 0·43, 0·98; P trend = 0·044), and after further adjustment for anthocyanin intake, the inverse association tended to be non-linear (Q4 v. Q1: RR = 0·65; 95 % CI 0·44, 0·98; P trend = 0·079). However, we did not find an association between glycaemic index-grouped fruit, glycaemic load-grouped fruit or other fruit subtype intake and GDM risk. Conclusions: In conclusion, specific fruit intake (particularly anthocyanin-rich fruit and grapes) but not total fruit intake was inversely associated with GDM risk.